Mediating role of information and communication technology between e-HRM and organizational performance in Pakistan - Rajeh Bati Almasradi; Saad Aziz Al-Otaibi; Muhammad Wasim Akram; Nazia Farheen; Shaza Mahar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Every year, businesses devote a substantial portion of their funds to purchase digital human resource management systems. The area is rapidly evolving, and a growing number of businesses are investing in e-HRM. The failure to embrace new technologies caused problems to textile sector to satisfy the operational demands of the industry. Quantitative approach is used to find the relationship between e-HRM, information communication technology (ICT) and organizational performance (OP) in textile industry of Pakistan. The study used a cluster sampling technique for data collection and SPSS and Smart-PLS software were used for data analysis. This study finds association between e-HRM and OP through ICT. It assists HR practitioners increasing their understanding of the essential role being played in achieving sustainably competitive advantage and company success by focusing on e-HRM activities. The key findings of this research emphasizes that e-HRM has an optimistic link with OP, which reduces costs and improves procedures so that quicker processes and functions may be performed. The study also provides theoretical and managerial implications.
Keywords: 330; organizational performance; electronic human resource management; information and communication technology; ICT; textile sector